2011
DOI: 10.1111/j.1365-2400.2011.00805.x
|View full text |Cite
|
Sign up to set email alerts
|

Using the Judas technique to locate and remove wintertime aggregations of invasive common carp

Abstract: Radio‐ and acoustic telemetry in three Midwestern lakes demonstrated that common carp, Cyprinus carpio L., aggregate as water temperatures descend below 10 °C. Particularly dense aggregations formed at temperatures <5 °C, and once located, these aggregations could be removed with an efficiency of up to 94% using seine nets. Carp aggregated just below the surface of the ice (approximately 1.5 m) and rarely descended to warmer waters, which extended down to 10 m. Although aggregations consistently formed close t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
110
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 23 publications
2
110
1
2
Order By: Relevance
“…Precise population estimates of adult carp were available for ten of the study lakes from ongoing mark-recapture studies (Bajer and Sorensen 2010;Bajer et al 2011;Osborne 2012; Table 1). In lakes for which mark-recapture data were not available, the abundance of carp was estimated using boat electrofishing in April-June and a regression relationship we developed using 4 years of census data [Density (carp/ha) = -0.48 ?…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Precise population estimates of adult carp were available for ten of the study lakes from ongoing mark-recapture studies (Bajer and Sorensen 2010;Bajer et al 2011;Osborne 2012; Table 1). In lakes for which mark-recapture data were not available, the abundance of carp was estimated using boat electrofishing in April-June and a regression relationship we developed using 4 years of census data [Density (carp/ha) = -0.48 ?…”
Section: Methodsmentioning
confidence: 99%
“…In the present study we employed a combination of correlative observations and controlled experiments to test the hypothesis that recruitment (and invasiveness) of the common carp can be explained by localized reductions in biotic resistance associated with seasonal declines in native micro-predators in unstable spawning habitat (Bajer and Sorensen 2010;Sorensen and Bajer 2011). We found strong evidence that native micro-predators and bluegill sunfish (Lepomis macrochirus) in particular, are able to control carp recruitment by exerting strong predatory pressure on carp eggs.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Commercial fisheries can cause nontarget impacts (e.g., bycatch); however, bycatch can be minimized by imposing size restrictions on fishing gear and identifying periods and locations of common carp aggregations (e.g., Diggle et al 2004;Penne and Pierce 2008;Bajer et al 2011). Additionally, harvest subsidies can replace market incentives to increase commercial harvest.…”
mentioning
confidence: 99%
“…We tagged 30 adult Carp (12 males and 18 females). A previous study showed that this approach (“Judas fish”) can be used to accurately describe overall Carp distribution and abundance (Bajer, Chizinski, & Sorensen, 2011). We re‐located these Carp 3 weeks later from a small boat using radio‐telemetry (manual bi‐angulation, a technique with an accuracy of about 20 m; Bajer & Sorensen, 2010) to confirm their health (all survived) and to pick a site that lacked Carp that could be used as a bait site.…”
Section: Methodsmentioning
confidence: 99%